Analysis of the "Zero Defects" Management Strategy in Improving the Quality of Inpatient Care Based on Crosby's 6 C Theory: A Case Study at Tongas Regional Hospital, Probolinggo Regency - Nindi Elis; Chusnuz Zaki; Victor Anaya (International Journal of Management Science, 2025)
This study focuses on the implementation of this strategy at RSUD Tongas in Probolinggo Regency, identifying challenges, and proposing solutions to optimize its implementation. The research employs a qualitative descriptive approach, emphasizing a deep understanding of the strategy's effectiveness. Data were collected through interviews, observations, and documentation from both primary and secondary sources. The "Zero Defects" management strategy based on Crosby's 6C theory has been well implemented at RSUD Tongas, focusing on eliminating errors in every aspect of inpatient care. This approach involves all staff, supported by strong management commitment, and includes intensive training, effective communication, and the formation of special teams to monitor and improve processes. Supporting factors include leadership commitment and an organizational culture that encourages innovation, while obstacles include resistance to change and limited resources. To overcome these challenges, RSUD Tongas needs to develop a more comprehensive quality assurance system and involve patients as partners in service improvement.